DIFFICULTIES IN TEACHING FOREIGN LANGUAGES AT HIGHER SCHOOLS AND THEIR EFFECTIVE SOLUTION - Barakatova Aminovna, Dilorom; KamalovaObidovna, Dilfuza; Azimova Fattokhevna, Nazira; Saidova Yorikulovna, Sayyora (International Journal of Psychosocial Rehabilitation, 2020)
Teaching a foreign language via different techniques should be directed to achieve the students’ ability to use the learning language for communication. Any teacher can attain this aim by taking into consideration the level and age of his or her students and their spiritual and emotional state. Moreover, according to the principle of creativity, student activity should be non-reproductive, productive, and creative; the student should be able to independently evaluate the situation and make independent decisions. Students’ attitude to their work and their responsiveness will increase their interest in the lesson.